2005
DOI: 10.1111/j.1523-1755.2005.00569.x
|View full text |Cite
|
Sign up to set email alerts
|

CREB mediates ERK-induced survival of mouse renal tubular cells after oxidant stress

Abstract: We show that survival during oxidant stress is mediated through CREB and identification of its downstream targets will reveal important survival pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
48
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 41 publications
4
48
0
Order By: Relevance
“…During I/R injury, the EGFR is activated in the proximal tubules of the kidney, but ERK activation is absent, and the proximal tubules undergo necrotic death (20,21). We made a similar observation in vitro: a high dose of H 2 O 2 causes necrotic (oncotic) death of renal proximal tubule cells with concomitant activation of the EGFR but not ERK, and ectopic activation of endogenous ERK rescues the cells from injury (14,15). On the other hand, during moderate stress (moderate dose of H 2 O 2 ) in vitro, renal proximal tubule cells survive through activation of the EGFR and ERK (14,15).…”
supporting
confidence: 49%
See 3 more Smart Citations
“…During I/R injury, the EGFR is activated in the proximal tubules of the kidney, but ERK activation is absent, and the proximal tubules undergo necrotic death (20,21). We made a similar observation in vitro: a high dose of H 2 O 2 causes necrotic (oncotic) death of renal proximal tubule cells with concomitant activation of the EGFR but not ERK, and ectopic activation of endogenous ERK rescues the cells from injury (14,15). On the other hand, during moderate stress (moderate dose of H 2 O 2 ) in vitro, renal proximal tubule cells survive through activation of the EGFR and ERK (14,15).…”
supporting
confidence: 49%
“…We made a similar observation in vitro: a high dose of H 2 O 2 causes necrotic (oncotic) death of renal proximal tubule cells with concomitant activation of the EGFR but not ERK, and ectopic activation of endogenous ERK rescues the cells from injury (14,15). On the other hand, during moderate stress (moderate dose of H 2 O 2 ) in vitro, renal proximal tubule cells survive through activation of the EGFR and ERK (14,15). These observations suggest that the activated EGFR could serve a prodeath function (22) in addition to its more widely accepted role of enhancing regeneration of the injured segments of the kidney (20,23,43,44).…”
mentioning
confidence: 95%
See 2 more Smart Citations
“…Of interest, a recent report indicated that CREB activation also plays a critical role in mediating Erk-1/2-induced tubular epithelial cell survival after oxidant stress. 33 Therefore, it is conceivable that CREB activation may be vital for mediating the beneficial effects of HGF by virtue of its ability to induce SnoN expression and to promote tubular epithelial cell survival. Consistently, attenuation of renal fibrosis and induction of SnoN after administration of HGF gene in vivo are closely correlated with the activation of Erk-1/2 and CREB in obstructive nephropathy ( Figure 9).…”
Section: Hgf Induces Erk-1/2 and Creb Activation In Vivomentioning
confidence: 99%